2018
DOI: 10.1140/epje/i2018-11683-x
|View full text |Cite
|
Sign up to set email alerts
|

From hydrodynamic lubrication to many-body interactions in dense suspensions of active swimmers

Abstract: We study how hydrodynamic interactions affect the collective behaviour of active particles suspended in a fluid at high concentrations, with particular attention to lubrication forces which appear when the particles are very close to one another. We compute exactly the limiting behaviour of the hydrodynamic interactions between two spherical (circular) active swimmers in very close proximity to one another in the general setting in both three and (two) dimensions. Combining this with far-field interactions, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 83 publications
(181 reference statements)
1
18
0
Order By: Relevance
“…However, hydrodynamic interactions can have a profound impact on the dynamical self-assembly of active colloidal systems, such as the suppression of MIPS [89][90][91][92] and the emergence of global polar ordering. [93][94][95][96][97] In systems of rotating particles, it is found that hydrodynamic interactions can induce cluster rotation, such that the overall cluster and the individual particles rotate in the same direction. 98 In the present work, we have seen that the giant Type I vortices and circle swimmers rotate in the same direction.…”
Section: Discussionmentioning
confidence: 99%
“…However, hydrodynamic interactions can have a profound impact on the dynamical self-assembly of active colloidal systems, such as the suppression of MIPS [89][90][91][92] and the emergence of global polar ordering. [93][94][95][96][97] In systems of rotating particles, it is found that hydrodynamic interactions can induce cluster rotation, such that the overall cluster and the individual particles rotate in the same direction. 98 In the present work, we have seen that the giant Type I vortices and circle swimmers rotate in the same direction.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of this approach is that the bend (splay) instability is expressed by m = 1 and ψ = Ar (ψ = Ar). It is also convenient to expand other vector fields such as velocity v and force f fields [45],…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Here, we have used incompressibility to simplify the rotational flow. Using the force generated by active stress (67), the cos θ terms in (69) and (70) result in L (a,a) in the linearized matrix (47) for the coefficients of the expansion (45), whereas sin θ terms result in L (b,b) .…”
Section: Stability Around Uniform Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…For these systems, the biggest difficulty comes from the need to accurately model the hydrodynamic interactions, which greatly increases the computational cost of the simulations. A brilliant solution to this problem is found in the article by Yoshinaga et al [5], where a new numerical scheme is developed which allows for the simulations of a large number of active particles that have accurate hydrodynamic interactions even when close to each other. The article shows that lubrication forces, often ignored in other methods, are in competition with long-range hydrodynamic forces, and can completely change the behaviour of swimmers.…”
mentioning
confidence: 99%